Notes on Australasian Orchids 6: A new species of Rhizanthella (Diurideae, subtribe Prasophyllinae) from Eastern Australia - Clements, Mark A.; Jones, David L. (Lankesteriana: International Journal on Orchidology, 2020)
Rhizanthella speciosa, a new species of the remarkable Australian underground orchids, is described as new from New South Wales. The new species, which is morphologically distinct and apparently also genetically distinct from its congeners and strikingly beautiful with its sea-anemone-like flowerheads and prominent attenuate sepals, grows in a different habitat than its geographically closest relative. Keywords: Australian orchid flora, New underground orchid, Orchidoideae, Rhizanthella speciosa